If f(x) = 3x + 1 and g(x) = 2x − 4, find f(g[2]).

asked Nov 11, 2012 in Algebra 1 Answers by anonymous

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:

To avoid this verification in future, please log in or register.

2 Answers

f(x)=3x+1, g(x)=2x-4

f(g(x))=3*(2x-4)+1=

=6x -12+1

=6x-11

at x=2, fg=1
answered Nov 12, 2012 by anonymous

find f(g[2]) solution;

g(2) = 2(2) − 4

        =0

f(0) = 3(0) + 1

      =1

so that,  

f(g[2])=1

answered Jun 19, 2013 by anonymous

Related questions

1 answer
asked Jan 24, 2013 in Algebra 2 Answers by anonymous | 95 views
0 answers
asked Mar 17, 2013 in Algebra 1 Answers by anonymous | 82 views
1 answer
1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
76,971 questions
80,453 answers
1,578 comments
58,243 users